Multidisciplinary approach on rehabilitation of primary teeth traumatism repercussion on the permanent successor: 6-year follow-up case report - Mello-Moura ACV; Bonini GAVC; Suga S; Navarro R; Wanderley M (Wolters Kluwer Medknow Publications, 2009)
Traumatic lesions in primary teeth are frequent in pediatric patients and can cause problems both to the deciduous tooth and permanent successor. The impact strength on deciduous tooth can reach the growing permanent tooth, affecting its morphology, structure and position, or even hampering its proper development. This report describes an aesthetic-functional rehabilitation process in an 8 year 10 month old boy during a multidisciplinary treatment held at the Clinical Center of Dental Trauma in Primary Teeth of the Pediatric Dentistry of Dental College of University of São Paulo, Brazil. The patient presented bilateral posterior cross bite and the permanent left upper central incisor with ectopic eruption and enamel hypoplasy, preceded by avulsion of element 61, occurred when the patient was 1.6 years old. After diagnosis and treatment planning, a quick expansion of jaws was recommended with Hass-type rapid expander and orthodontic leveling with fixed braces. Due to the ectopic eruption, the gingival contour had been altered and hypertrophia was found, compromising aesthetics and avoiding local hygienic procedures. Gingivoplasty was carried out with high-intensity Diode Laser, followed by aesthetic restoration with compound resin. It was concluded that after deciduous teeth traumatism it is important that the patient undergoes clinic and radiographic assistance until the permanent teeth erupt so that an adequate multidisciplinary treatment can be offered to the patient.